Influence of Moisture Content on Creep Mechanical Characteristic and Mic-Fracture Behavior of Water-Bearing Coal Specimen - Zhong Zhao; Peng Wu; Lan Wang; Ming Li; Xianbiao Mao; Liang Chen (Geofluids, 2022)
The most challenging aspect of constructing an underground reservoir is ensuring that the safety coal pillar has long-term stability. It is of great significance to study the creep mechanical behavior of coal pillars under water-rock interaction for the construction of underground reservoirs. Five kinds of coal specimens with different moisture contents (dry, 2.42%, 5.53%, 7.55%, and saturated) were prepared. The effect of moisture content on the creep mechanical behavior of coal specimens was studied by graded loading, and the acoustic emission signals during the creep loading of coal specimens were monitored. The results showed that with the increase in moisture content, the instantaneous strain and creep strain of coal specimens gradually increase, and the total time of the creep test, creep failure stress, and long-term strength generally decreases. The creep failure stress to peak strength and the ratio of long-term strength to peak strength were 73%~85% and 57%~65%, respectively, which are basically independent of water content. As the water content of the coal increased, the cumulative acoustic emission energy decreased, and the failure form of the coal specimen gradually shifted from tension failure (ω=0% and 2.42%), tension shear composite failure (ω=5.53%) to shear failure (ω=7.55% and 10.08%). The research results can be used as a reference for the design and strength evaluation of coal pillars for underground reservoirs in coal mines.